1970
DOI: 10.1063/1.1658462
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Expansion of Polyethylene Unit Cell: Effect of Lamella Thickness

Abstract: The unit cell dimensions have been measured at temperatures between 93 and 333 K for linear polyethylene samples with long periods of 385, 220, and 99 Å. The angular positions of 6 x-ray diffraction lines were obtained at 5–10 K intervals with a powder diffractometer and the positions corrected for beam penetration so as to agree with powder camera results obtained with more lines at 296 and 155 K. At lower temperatures, the cell dimensions are nearly independent of long period, but at higher temperatures, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
1
1

Year Published

1972
1972
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(89 citation statements)
references
References 29 publications
8
79
1
1
Order By: Relevance
“…This behavior would be analogous to the effect of amorphous surfaces on the lattice spacing of polyethylene crystals 17 18, for which it was found that this spacing decreases with increasing lamellar thickness.…”
Section: Discussionmentioning
confidence: 99%
“…This behavior would be analogous to the effect of amorphous surfaces on the lattice spacing of polyethylene crystals 17 18, for which it was found that this spacing decreases with increasing lamellar thickness.…”
Section: Discussionmentioning
confidence: 99%
“…In the work [19], lattice parameters a, b, c have been measured in the temperature range 93 -333 K, and the data are smooth enough to allow a direct extraction of thermal expansion coefficients by means of finite differences. The other chosen set of data [20] is to our knowledge the only one covering the range from helium temperatures up to T = 350 K, however, the scatter of the data is too large for a direct numerical differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…From their work on the x-ray spacings of lamellar bulk polyethylene samples and single crystals, Davis, Eby, and Colson [15] Here A 0 is the cross-sectional area of the chain in an undisturbed lattice at a specified temperature in ,42 for polyethylene, and A o(strain) the same quantity for a sample with a finite lamellae of thickness 12 that exhibits an expanded lattice resulting from end surface stress. 6 The value of K2 in A 3 has been given by these authors for meltcrystallized polymer, solution crystallized polymer, and nparaffins, and highly precise values of Ao are available from the same source [16].…”
Section: Estimate Of the Lattice Expansion Resulting Frommentioning
confidence: 99%
“…This assumption cannot be made in cases where there are no physical grounds for deciding that the surface free energy depends on the dimensions of the system considered. and in a similar way we obtain Given the free energy of formation in ergs/crystallite as (23) (20e) and inserting (T e from eq (21), there is obtained r (24) whi c h beco mes, on noting from eq (15) (25) where the volume strain parameter a is defined as…”
Section: (20£)mentioning
confidence: 99%